The Role of Fifth-Grade Teachers in IPAS Learning at SD Negeri 01 Ulak Karang Padang - Alfarida, Dhora; Efendi , Nofriza; Efrina, Gusnita; Stavinibelia, Stavinibelia (The Future of Education Journal, 2025)
This research was conducted due to the minimal role of teacher in IPAS learning. Research background this study is based on the observation that many students exhibit poor behavior and during lessons delivered by the teacher at the front of the class, many students do not focus on paying attention. It is also evident that the teacher has not fully implemented their role in the learning process; for example, the teacher does not provide reflection at the end of the lesson and has not been able to create a conducive and enjoyable learning atmosphere. This research aims to describe the role of the fifth-grade teacher in teaching Natural and Social Sciences (IPAS) at SD Negeri 01 Ulak Karang Padang. This study uses a qualitative approach. The subjects of the research are the fifth-grade homeroom teacher and the fifth-grade students. Data collection techniques include observation, interviews, and documentation. Data analysis is conducted through stages of data reduction, data presentation, and conclusion drawing. Based on the results obtained, the teacher in the classroom during IPAS lessons plays the roles of facilitator, motivator, and guide. The teacher needs to better implement their role during the learning process. The teacher should also stimulate students’ enthusiasm and motivation to learn IPAS. The teacher is encouraged to maximize their roles as motivator, facilitator, and guide.